Immunocytochemical localization of basic fibroblast growth factor in squamous cell carcinomas of the head and neck - Riedel, Frank; Götte, Karl; Oulmi-Kagermann, Jasmina; Hörmann, Karl (Anticancer research, 2001)
Angiogenesis is crucial for tumour growth and formation of metastasis. Basic fibroblast growth factor (bFGF) is known to have potent angiogenic activity and has been identified in a wide variety of malignancies including head and neck squamous cell carcinomas (HNSCC). Clarification of its localization in HNSCC is important for the understanding of angiogenesis. Cryosiat sections of 27 HNSCC were immunostained for bFGF using a standard streptavidin-biotin complex procedure. Western blot analysis revealed three immunoreactive bFGF isoforms of 18, 22 and 24 kDa. Immunohistochemical and -cytochemical localization of bFGF was studied at light and electron microscopic levels. bFGF was mainly localized within the focal tumoral areas rather than in the tumour stroma. On a subcellular level, the ultrastructural investigation showed electron-dense bFGF localization in the cytosol of the carcinoma cells, but bFGF labelling within the nuclei of HNSCC cancer cells was one prominent finding of this study. In conclusion, the presence of bFGF isoforms in most of the cancer cells supports the theory of a direct paracrine mechanism of bFGF from cancer cells on tumour angiogenesis. The nuclear localization of bFGF in the HNSCC cells supports its activity as a transcriptional factor.